Test of effectiveness decompocers on some types of compost material - Budi Ananda Pratama; Tengku Sabrina; Mariani Sembiring (Talenta Publisher, 2019)
Organic residues resulting from agricultural activities are nutrients for plants, but must go through a process of decomposition by soil microorganisms called decomposers. This study aims to examine the effect of several types of decomposers on several types of compost materials. This research was conducted at university faculty of agriculture of North Sumatera. This research was conducted starting from November 2017 - January 2018. In this research the design used is factorial randomized block design consisting of 2 factors of treatment that is compost material (TKKS, bagasse, straw) and decomposer type comes from, (TKKS, Bagasse, straw). the results showed that the compost material derived from TKKS was compost material containing N-total 1.31%, K-total 0.880%, C-organic 34.02%, C / N 30.51% and total microbial 2.5 x 108 CFU, higher than other compost materials. Decomposers derived from TKKS are decomposers capable of lowering the C / N ratio lower than the decomposers derived from other materials of 26.59, with total K-content of 0.556%, higher than others, C-organic 23.79% lower than others , but the highest N-total content comes from straw material that is 0.94%. The interaction between the compost and the decomposer derived from the isolates reduced C-organic and C / N lower than the others, but the reaction from the original decomposer to the N-total content of the TKKS was higher at 1.24%, the lower bagasse, 1.10 % and higher straw is 0.72% and K-total compost from TKKS is 0.91%, bagasse 0.21% and straw lower is 0.22%.